Applying Surface-Based DNA Computing for Solving the Dominating Set Problem - Taghipour, Hassan; Rezaei, Mahdi; Esmaili, Heydar A. (Scientific Research Publishing, 2012)
The surface-based DNA computing is one of the methods of DNA computing which uses DNA strands immobilized on a solid surface. In this paper, we applied surface-based DNA computing for solving the dominating set problem. At first step, surface-based DNA solution space was constructed by using appropriate DNA strands. Then, by application of a DNA parallel algorithm, dominating set problem was resolved in polynomial time.
Keywords: Parallel Computing; Surface-Based DNA Computers; Dominating Set Problem; NP-Complete Problem